2021
DOI: 10.1029/2020wr029528
|View full text |Cite
|
Sign up to set email alerts
|

The Limits of Homogenization: What Hydrological Dynamics can a Simple Model Represent at the Catchment Scale?

Abstract: Large‐scale models often use a single grid to represent an entire catchment assuming homogeneity; the impacts of such an assumption on simulating evapotranspiration (ET) and streamflow remain poorly understood. Here, we compare hydrological dynamics at Shale Hills (PA, USA) using a complex model (spatially explicit, >500 grids) and a simple model (spatially implicit, two grids using “effective” parameters). We asked two questions: What hydrological dynamics can a simple model reproduce at the catchment scale? … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 125 publications
(178 reference statements)
1
8
0
Order By: Relevance
“…Such analyses underscore the importance of horizontal, or landscape, connectivity in shaping export patterns under certain conditions. Given the multiple dimensions (e.g., vertical, horizontal) of flow in catchments, it is possible that different flow paths activated under varying connectivity conditions influence solute export patterns to varying degrees (Wen et al., 2021; Xiao et al., 2019), potentially leading to non‐monotonic CQ patterns. To investigate complex CQ behavior, some authors have suggested splitting CQ plots at threshold discharge values and determining separate CQ patterns and underlying mechanisms at different flow regimes (Moatar et al., 2017; Underwood et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Such analyses underscore the importance of horizontal, or landscape, connectivity in shaping export patterns under certain conditions. Given the multiple dimensions (e.g., vertical, horizontal) of flow in catchments, it is possible that different flow paths activated under varying connectivity conditions influence solute export patterns to varying degrees (Wen et al., 2021; Xiao et al., 2019), potentially leading to non‐monotonic CQ patterns. To investigate complex CQ behavior, some authors have suggested splitting CQ plots at threshold discharge values and determining separate CQ patterns and underlying mechanisms at different flow regimes (Moatar et al., 2017; Underwood et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The model can be used broadly as an organizing framework to understand competing processes that regulate mean solute concentrations. More complex reactive transport models at the watershed scale can be used to complement such simple models and to examine detailed processes, variables, and spatial heterogeneities that reflect idiosyncrasies of specific sites (Li, 2019; Wen et al., 2021; Wen et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…This indicates that the 30-m depth of the subsurface domain may be insufficient to capture all groundwater baseflow. Our model consistently overestimates the baseflow, which is likely due to the limit of spatial homogenization for hydrological dynamics discussed in Wen et al (2021). Further, the model assumes that groundwater in the subsurface does not freeze, which leads to an overestimation of groundwater discharge in winter.…”
Section: Limitationsmentioning
confidence: 81%